The development of value perception toward cultural tourism destination: a Northeast Thailand case study / Ann Suwaree Ashton, Suchawadee Limisariyapong and Rasmee Islam - Ashton, Ann Suwaree; Limisariyapong, Suchawadee; Islam, Rasmee (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
This study aims to measure value perception toward cultural tourism destination. This study employs a quantitative approach and uses a survey questionnaire form for the data collecting process. A total of 212 samples were collected and multiple regression techniques were used to analyze data. The findings revealed that five value components, including functional, social, emotional, epistemic and conditional, influence tourist satisfaction and intention to revisit the destination. This study provides insight knowledge for both academic and managerial contributions. For the academic part, this study offers foundation knowledge on perceived value toward cultural tourism development theory. In terms of managerial contribution, the findings of this study are useful for several stakeholders, such as the outcome can help local authorities and communities develop destinations by adding value. Notably, the most effective way to promote a cultural tourism destination is best done through online marketing and by having influential community leaders.